Average Deactivation Time of the Heterogeneous Reaction 2A+B2→2AB - Pastor, Verónica Estela (2014)
In the present paper we exactly solve the distributed parameter stochastic model of the heterogeneous catalytic reaction 2A+B2→2AB and calculate the average number of reactive steps necessary to deactivate the lattice first,< t >. Results are compared with Monte Carlo simulations.< t >shows a nonmonotonic behavior with the sticking coefficient probabilitys and the desorption probability pd, reaching a maximum value that depends on s,pd and the lattice size N.